Nada. (Sarajevo : [Zemaljska štamparija], 1895)
"Pouci, zabavi i umjetnosti."
Title from caption.
Mode of access: Internet.
In Bosnian (Roman), Serbian (Roman), and Croatian.
Latest issue consulted: Godina 3, broj 24 (15. decembra 1897).
Description based on: Godina 1, broj 1 (1. januara 1895); title from caption.
Keywords: Slavic literature, Southern; Slavic literature, Southern -- Periodicals; Periodicals